A ALFABETIZAÇÃO DO SURDO: UMA NECESSIDADE DE COMPREENSÃO DO DIFERENTE - Mendes, Paulo Eduardo (Intercâmbio, 2010)
We analysed some interactional aspects of the Literacy Process in two deaf children schools, based on Oralism and Total Communication. We realized that these methods are more concerned about the rehabilitation of the deaf than about his/her learning process.